2012
DOI: 10.1038/srep00239
|View full text |Cite
|
Sign up to set email alerts
|

Short Co-occurring Polypeptide Regions Can Predict Global Protein Interaction Maps

Abstract: A goal of the post-genomics era has been to elucidate a detailed global map of protein-protein interactions (PPIs) within a cell. Here, we show that the presence of co-occurring short polypeptide sequences between interacting protein partners appears to be conserved across different organisms. We present an algorithm to automatically generate PPI prediction method parameters for various organisms and illustrate that global PPIs can be predicted from previously reported PPIs within the same or a different organ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
63
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 59 publications
(63 citation statements)
references
References 24 publications
0
63
0
Order By: Relevance
“…Our new methods and new predictions 57 at least double the number of organisms for which sequence-based PPI predictions are 58 available, and they do this in a more consistent way than other method [24]. On top,…”
mentioning
confidence: 84%
See 1 more Smart Citation
“…Our new methods and new predictions 57 at least double the number of organisms for which sequence-based PPI predictions are 58 available, and they do this in a more consistent way than other method [24]. On top,…”
mentioning
confidence: 84%
“…As before in [20], [23], we obtained Many advanced sequence-based PPI prediction methods have been developed. Park and 112 Marcotte [22] showed that PIPE2 [24], AutoCorrelation [31], and SigProd [32] 113 performed well compared to other methods. We showed a profile-kernel SVM to improve 114 over these methods for human and yeast [23].…”
mentioning
confidence: 98%
“…Thus, there is a longstanding interest in using sequence-based methods to model and predict protein interactions (Hashemifar, et al, 2018). Several sequence-based methods have been developed to predict PPIs, such as SigProd (Martin, et al, 2005), AutoCorrelation (Guo, et al, 2008), Yang's work (Yang, et al, 2010), Zhou's work (Zhou, et al, 2011), PIPE2 (Pitre, et al, 2012), You's work (You, et al, 2014), PPI-PK (Hamp and Rost, 2015), Wong's work (Wong, et al, 2015), Sun's work (Sun, et al, 2017), and DPPI (Hashemifar, et al, 2018). The main limitation of these sequence-based methods is only the amino acid compositions of a sequence were considered.…”
Section: Introductionmentioning
confidence: 99%
“…PIPE has been used to identify novel protein interactions, to discover new protein complexes, to predict novel protein functions [3236], and to produce proteome-wide predicted interaction networks for S . cerevisiae [34], Schizosaccharomyces pombe [33], Caenorhabditis elegans [35] and Homo sapiens [36], among others.…”
Section: Introductionmentioning
confidence: 99%
“…We do note that interactions from one species can be used to predict interactions in another, even using distant relatives such as human and yeast. However, within-species interactions have been found to be more accurate [33]. …”
Section: Introductionmentioning
confidence: 99%